Long-term outcome of hemiarch replacement in a proximal aortic aneurysm repair: analysis of over 1000 patients. (3rd February 2022) - Pearsall, Christian; Blitzer, David; Zhao, Yanling; Yamabe, Tsuyoshi; Rajesh, Kavya; Kim, Ilya; Bethancourt, Casidhe; Hu, Diane; Bergsohn, Josh; Kurlanksy, Paul; George, Isaac; Smith, Craig; et al.
Abstract: OBJECTIVES: The aim of this study was to investigate the impact of hemiarch replacement in patients undergoing an open repair of proximal thoracic aortic aneurysm without arch aneurysm. METHODS: A retrospective review was performed on 1132 patients undergoing proximal aortic aneurysm repair at our Aortic Center between 2005 and 2019. Inclusion criteria were all patients undergoing root or ascending aortic aneurysm repair with or without hemiarch replacement. Exclusion criteria were age <18 years, aortic arch diameter ≥4.5 cm, type A aortic dissection, previous ascending aortic replacement, ruptured aneurysm and endocarditis. Propensity score matching in a 2:1 ratio (573 non-hemiarch: 288 hemiarch) on 19 baseline characteristics was performed. The median follow-up time was 46.8 months (range 0.1–170.4 months). RESULTS: Hemiarch patients had significantly lower 10-year survival in the matched cohort (hemiarch 73.8%; 66.9–81.4%; vs non-hemiarch 86.5%; 81.1–92.3%; P < 0.001), driven by higher in-hospital mortality rate (4% vs 1%; P < 0.001). Cumulative incidence of aortic arch reintervention rates at 10 years was similarly low (hemiarch 1.0%; 0–2.5% vs non-hemiarch 1.3%; 0–2.6%, P = 0.615). Multivariate analysis with hazard ratios of the overall cohort showed hemiarch as an independent factor associated with long-term mortality (2.16; 1.42–3.27; P < 0.001) but not with aortic arch reintervention (0.76; 0.14–4.07, P = 0.750). CONCLUSIONS: Hemiarch repair may be associated with higher short-term mortality compared to non-hemiarch. Arch reintervention was rare after a repair of proximal thoracic aortic aneurysm without arch aneurysm. Our data call for larger and prospective studies to further delineate the utility of hemiarch repair in proximal aortic surgery. Abstract : Indications for surgical repair of a proximal thoracic aortic aneurysm, defined as a repair of the aortic root or ascending aorta, include size, growth rate and the presence of symptoms.